2003
DOI: 10.1159/000071333
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Variceal Bleeding

Abstract: Portal hypertension as a consequence of liver cirrhosis is responsible for its most common complications: ascites, spontaneous bacterial peritonitis, hepatorenal syndrome, hepatic encephalopathy and the most important one – variceal hemorrhage. Variceal bleeding results in considerable morbidity and mortality. This review covers all areas of importance in the therapy of acute variceal hemorrhage – endoscopic and pharmacological treatment, transjugular intrahepatic portosystemic shunt, surgery and balloon tampo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 69 publications
0
19
0
1
Order By: Relevance
“…Octreotide, a long-acting analogue of somatostatin, has been reported to be useful for the treatment of acute esophageal variceal haemorrhage and the prevention of early rebleeding, in studies predominantly carried out in the U.S. [10,14]. Recent meta-analyses showed that octreotide stopped esophageal variceal bleeding in about 81-86% of cases examined [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide, a long-acting analogue of somatostatin, has been reported to be useful for the treatment of acute esophageal variceal haemorrhage and the prevention of early rebleeding, in studies predominantly carried out in the U.S. [10,14]. Recent meta-analyses showed that octreotide stopped esophageal variceal bleeding in about 81-86% of cases examined [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Varices are caused by portal hypertension and develop when the portal pressure gradient exceeds 10 mm Hg, resulting in the development of portosystemic collateral circulation. 2,[32][33][34][35][36][37][38][39]76 Gastroesophageal collaterals develop via connections from the short gastric and coronary veins and the esophageal, azygos, and intercostal veins. Other collaterals may develop giving rise to anorectal varices, umbilical or paraumbilical varices, and splenorenal shunts.…”
Section: Variceal Hemorrhagementioning
confidence: 99%
“…The annual risk is 1% to 2% for patients with no evidence of varices at endoscopy and increases to 5% to 6% in patients with small varices and 15% in those with medium-tolarge varices ð!5 mmÞ. 2,[32][33][34][35][36][37][38][39] Patients with small varices and advanced liver disease ðeg, CPT class CÞ have similar rates of hemorrhage as those with large varices. Patients with cirrhosis should be screened, via endoscopy, for the presence of varices.…”
Section: Variceal Hemorrhagementioning
confidence: 99%
“…Esophageal varices, representing the clinically most relevant portosystemic collaterals, affect about 50% of patients with newly diagnosed liver cirrhosis [5] . In the case of portal hypertension 1 12 mm Hg, the incidence of variceal bleeding is increasing and affects 30% of patients with compensated liver disease and up to 60% of patients with decompensated liver disease [6] .…”
Section: Complications Of Portal Hypertensionmentioning
confidence: 99%
“…This includes sclerotherapy, application of tissue adhesives, banding of varices, and some other methods. Variceal banding is more diffi cult in acute bleeding due to less visibility, but can control bleeding as effectively as sclerotherapy with less complications and thus seems to improve survival compared to sclerotherapy [6] .…”
Section: Options For Treatment Prior To Liver Transplantationmentioning
confidence: 99%